Grace Lee Boggs : gardens of hope - Daemicke, Songju Ma (Albert Whitman & Company, 2025)
"When Grace Lee Boggs was eight years old, her teacher gave her a copy of The Secret Garden. As a Chinese American, Grace had experienced prejudice, and she wanted to grow a garden of her own that would help people heal from injustice. Grace dedicated her life to fighting for civil, environmental, labor, and women's rights. In 1992, she and her husband founded Detroit Summer, a multicultural and intergenerational youth program that inspired kids to become leaders in their community. Together with these "solutionaries," Grace finally created the garden she dreamed about, one that continues to inspire people to make the world a better place for everyone"-- Provided by publisher.